“You feel like you come up short over and over again”: a qualitative study of provider perspectives of barriers to respectful maternity care in Boston - Katherine Fachon; Sahana Narayan; Samantha Truong; Christina Duzyj; Katherine Vergara Kruczynski; Amber Trujillo Lalla; Autumn Cohen; Patricia Barbosa; Amanda Flynn; Annekathryn Goodman (Reproductive Health)
Abstract Background Respectful maternity care is a human right. Disrespect in childbirth has been implicated in adverse maternal and child outcomes globally, including in the United States. Up to 30% of U.S. birthing people report being disrespected when giving birth, with reported rates being higher amongst racial/ethnic minorities and those who do not primarily speak English. Disrespect in childbirth leads to increased rates of postpartum depression and lower healthcare utilization. Methods Semi-structured qualitative interviews were conducted with 18 maternity health care providers at Massachusetts General Hospital in Boston, Massachusetts. Respondents included physicians, midwives, and nurses. Transcripts of the interviews were coded using an inductive approach, and themes were developed from the codes. Results Four major themes emerged: (1) patient-provider communication and dynamics, (2) structural and organizational drivers of care, (3) patterns in disrespect, and (4) clinician knowledge and beliefs about respectful and disrespectful care. Key barriers to respectful care included workload, facility infrastructure, and constraints in the provision of clinical care. Providers perceived that certain social vulnerabilities (e.g., race, age, ethnicity, language) predisposed some patients to greater levels of disrespect. Consent processes and procedures were also identified to be a crucial leverage point in preventing disrespectful maternity care. Conclusion Although respondents generally perceived care to be of high quality, they noted that challenges to respectful maternity care are present even in high-resource settings. Future research in disrespect and abuse in maternity care is necessary to further develop sustainable solutions. It is imperative to continue exploring the perspectives of maternity care providers, as they are key stakeholders and are uniquely positioned to identify root causes of mistreatment in care provision.